2019
DOI: 10.1021/acs.joc.9b00825
|View full text |Cite
|
Sign up to set email alerts
|

Hyperconjugative π → σ*CF Interactions Stabilize the Enol Form of Perfluorinated Cyclic Keto–Enol Systems

Abstract: Lindner and Lemal showed that perfluorination of keto-enol systems significantly shifts the equilibrium toward the enol tautomer. Quantum mechanical calculations now reveal that the shift in equilibrium is the result of the stabilization of the enol tautomer by hyperconjugative π → σ* CF interactions and the destabilization of the keto tautomer by the electron withdrawal induced by the neighboring fluorine atoms. The preference for the enol tautomer further increases in smaller perfluorinated cyclic keto-enol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
5
0
3
Order By: Relevance
“…This observation leads us to the explanation of the enol-promoting effect of electron-withdrawing groups. A number of previous studies , have indicated that electron-withdrawing groups can destabilize the keto (or, more generally, the carbonyl functional group) due to a decreased resonance stabilization. Notably, α-carbonyl electron-withdrawing substituents are expected to destabilize the resonance forms IV and VI in Scheme , since it is unfavorable to have an electron-withdrawing group adjacent to an electron-deficient carbon.…”
Section: Resultsmentioning
confidence: 99%
“…This observation leads us to the explanation of the enol-promoting effect of electron-withdrawing groups. A number of previous studies , have indicated that electron-withdrawing groups can destabilize the keto (or, more generally, the carbonyl functional group) due to a decreased resonance stabilization. Notably, α-carbonyl electron-withdrawing substituents are expected to destabilize the resonance forms IV and VI in Scheme , since it is unfavorable to have an electron-withdrawing group adjacent to an electron-deficient carbon.…”
Section: Resultsmentioning
confidence: 99%
“…More generally speaking, most enols are short-lived reactive species and they readily isomerize to their ketoforms; enols can be stabilized through resonance, [23] steric factors, [1] and electronic effects. [2,24] Experimental methods such as time-resolved spectroscopy, [5,25] neutralization-reionization mass spectrometry, [26,27] NMR as well as IR spectroscopy, [28] and other spectroscopic techniques [29] along with computational methods [30][31][32][33] have played a significant role in understanding the structures and reactivities of enols. The simplest enol, ethenol (vinyl alcohol), was generated in the gas phase through the pyrolysis of ethylene glycol.…”
mentioning
confidence: 99%
“…但全氟代环丁烯醇的稳定性却比全氟代环戊烯醇的稳定性大 [4] 。这是因为四元环中的 σ CF 键与 π 键 的空间距离比五元环中的 σ CF 键与 π 键的空间距离更近(见图 8b 中 VB 理论电子轨道示意图),具有 更大的重叠程度,即更大的共轭程度所致 [4] [27] 。这是因为 I 式中氧原子上含孤对电子的 p 轨道与反键分子轨道 σ * CCl 几 乎平行,重叠程度比较大,可以形成更低能量的分子轨道,即形成更稳定的 p-σ * CCl 超共轭体系。这 种现象被称为异头效应(anomeric effect),是 Edward [28] 于 1955 年首次在吡喃糖中发现的。σ-n 超共 轭对反应活性也有很大影响。如图 10b 所示,由于 σ CSi 比 σ CH 具有更强的给电子能力,可以与碳正 离子的空 p 轨道形成更稳定的 σ-n 超共轭体系,使得仅仅将 H 换成 SiCH 3 的消除反应速率增大 2.4 × 10 12 倍 [29] 。 3.2.3 σσ 超共轭体系结构特征 σ-σ 超共轭体系是指由于相邻的 σ 键电子轨道的重叠而形成的超共轭体系。如图 11a 所示,乙 烷分子具有两个典型的构象,即能量最高的重叠式和能量最低的交叉式。有关交叉式构象比重叠式 构象稳定的原因,有机化学教材上的解释是重叠式中非键氢原子之间的距离(229 pm)小于两个氢原 子范德华半径之和(240 pm) [9] (图 11b)或者认为是重叠式中 C-H 键上的 σ 电子对的排斥力较大 [30] (图 11c)。 1939 年, Mulliken [6] 首次指出超共轭效应是乙烷交叉式更稳定的主要原因。 2001 年, Vojislava Pophristic 和 Lionel Goodman [31] 指出交叉式构象中含电子的 σ CH 成键分子轨道与空的 σ * CH 反成分子 键轨道重叠形成了更稳定的分子轨道,即形成了 σ CH -σ * CH 共轭体系,从而使交叉式构象更稳定(σ CHσ * CH 轨道重叠图如图 11d 所示)。超共轭效应是乙烷交叉式更稳定的主要原因得到了一些实验及理 论的支持 [32] 图 10 σ-n 超共轭对分子结构及反应活性的影响 a) σn 超共轭对 2-氯四氢-2H-吡喃构象的影响 [27] ;b) σ-n 超共轭效应对消除反应活性的影响 [29] H [33] 和 3-氟-N,N-二甲基 哌啶正离子 [34] [33] ;b) 3-氟-N,N-二甲基哌啶正离子的两种椅式构象 [34] ; c) Z-和 E-1,2-二氟乙烯 [35] 电子版为彩图 空间超共轭体系中的原子或原子团的相对位置也比前面的空间共轭体系复杂。根据形成超共轭 体系的原子或原子团是连接同一碳原子上的原子或原子团、还是连接在单键或双键两端的邻位原子 或原子团、还是非直接相连的原子或原子团,Alabugin 等 [5] 将超共轭体系分为同位(geminal)、邻位 (vicinal)和远程(remote)原子或原子团轨道相互作用的超共轭体系(如图 13a-c 所示)。 这里的远程超共 轭类似前面讨论的空间共轭,可以发生在分子内,也可以发生在分子之间。分子内的远程超共轭体 系可以是通过中间间隔多个价键的原子或基团。如图 13c 所示,在 3-(三甲基硅烷基)丙基正离子中 相隔两个 σ 键(标示红色的两个 σ 键)的碳正离子与 C-Si 基团发生 σ CSi-p 超共轭 [37] 。远程超共轭体 系也可以是分子间相邻的原子或基团。如图 13c 所示的三氟甲烷中的 C-H 基团与水分子中的氧原 子之间形成的 σ CH-p 超共轭 [38]…”
Section: 分子内的 Ts-共轭体系结构特征unclassified
“…不同类型和程度的共轭效应。共轭效应是有机化学课程的重点和难点内容,掌握共轭体系的分类及 结构特征,对理解化合物的共轭效应具有重要作用。但一般的有机化学教材及文献对此没有系统的 介绍。一般大学有机化学教材只是在讨论 1,3-丁二烯独特的结构与性质时,简单地把共轭体系定义 为:键长平均化,共轭体系中的各原子共平面并有一个垂直于该平面的 p 轨道,以及各原子上的 p 轨道互相平行并重叠的电子流域结构体系。而把碳氢 σ 单键(σ CH )与 π 键或 p 轨道重叠而形成的电子 流域体系称为超共轭体系。随着共轭体系的深入研究,共轭体系的内涵已远远超出了一般大学有机 化学教材对共轭体系的定义,如文献报道的空间共轭 [1,2] 、含饱和碳原子的芳香体系 [3] 、碳-氟 σ 单 键(σ CF )参与的超共轭 [4] 等。本文综述了共轭体系的类型及结构特征,以拓展共轭体系在有机化学教 学中的内涵,加深师生对共轭体系及共轭体系对化合物结构与性质影响的理解。因为共轭体系与 π 键和 σ 键有关,本文在介绍共轭体系的分类及结构特征前,先简单地介绍 π 键与 σ 键在价键(valence bond,VB)理论以及分子轨道(molecular orbital,MO)理论中的表示方法。然后通过实例的结构式、 VB 及 MO 理论的电子轨道示意图,阐明共轭体系的分类及其结构特征。 1 VB 及 MO 理论中的共价键形成示意图 共轭体系一般是根据参与共轭的电子轨道类型来进行分类。为了更好地理解共轭体系的分类及 结构特征,我们需要先了解一下 VB 及 MO 理论对共价键的定义及电子轨道示意图。VB 理论认为 共价键的本质是原子相互接近时,原子价层的电子轨道(n 电子轨道)重叠(波函数叠加),原子间通过 共用自旋相反的电子对,使能量降低而形成的化学键。原子轨道重叠具有方向性,轨道以头碰头方 式重叠形成电子云呈键轴对称的 σ 键,以肩并肩方式重叠形成电子云呈面对称的 π 键。图 1a 为原子 的 n 电子轨道(s、p 和 sp x 杂化电子轨道,x = 1-3)重叠形成 σ 键和 π 键的示意图。图中原子轨道重叠 示意图和成键轨道图是 σ 键和 π 键的两种表示方法,常常在讨论反应机理、电子效应及共轭体系时 使用。除了这两种表示方法外,还有大家熟悉的短横线"-"和电子对""表示法。…”
unclassified